2018
DOI: 10.1037/dev0000519
|View full text |Cite
|
Sign up to set email alerts
|

Twin classroom dilemma: To study together or separately?

Abstract: There is little research to date on the academic implications of teaching twins in the same or different classroom. Consequently, it is not clear whether twin classroom separation is associated with positive or negative educational outcomes. As a result, parents and teachers have insufficient evidence to make a well-informed decision when twins start school. This study addresses two research questions: Are there average positive or negative effects of classroom separation? Are twins taught in different classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…We endorse this "hands off " policy but emphasize that teachers, administrators and parents need to keep each case under review, particularly in the early years, as the twins themselves may not react in the ways anticipated. It may be comforting to know, however, that available research on academic effects of separation indicates that there are no significant, systemic effects on academic outcomes of separating vs. keeping twins together (White et al, 2018).…”
Section: Policymentioning
confidence: 99%
“…We endorse this "hands off " policy but emphasize that teachers, administrators and parents need to keep each case under review, particularly in the early years, as the twins themselves may not react in the ways anticipated. It may be comforting to know, however, that available research on academic effects of separation indicates that there are no significant, systemic effects on academic outcomes of separating vs. keeping twins together (White et al, 2018).…”
Section: Policymentioning
confidence: 99%
“…A recent study by White et al (2018) has examined the effects of twins’ classroom placement on achievement, ability, and motivation. Samples included twins from Canada (ages 7–12 years) and England (ages 7–14 years), organized according to whether they were in the same classroom or separate classrooms.…”
Section: Same or Separate Classroomsmentioning
confidence: 99%
“…However, by age 12 these differences were not significant anymore, implying that there are not long-lasting effects of classroom separation. Contrarily, White et al found small effects of classroom separation on school achievement at age 12 and 16, while no differences between separated and non-separated twins were found at ages 7 to 10 [38].…”
Section: Introductionmentioning
confidence: 99%